1992
DOI: 10.1111/j.1755-618x.1992.tb02435.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Self‐referenced’ relative deprivation and economic beliefs: the effects of the recession in Alberta*

Abstract: Dans cette communication, les auteurs examinent un modèle théorique selon lequel le sentiment de vivre une privation relative joue un rôle important dans la traduction de l'expérience de difficultés économiques en une ‘idéologie économique’ plus à gauche sur le spectre des options politiques. Les données de l'enquête révèlent que les Albertains qui ont dû réduire leurs dépenses en raison de la récession du milieu des années 1980 avaient effectivement plus tendance à s'associer à des énoncés affirmant la nécess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Classic research relating macroeconomic downturns to hate crimes (e.g., Hepworth & West, 1988) as well as evidence from the analysis of national surveys indicating a strong correlation between change in the rate of unemployment over time and the level of popular opposition toward immigrants and immigration policy (see Palmer, 1996) suggest that in the RD condition, students will express more negative attitudes toward outgroups (see also Krahn & Harrison, 1992). As Gurr (1970) or Davies (1962) would argue, when economic conditions are getting worse, people may perceive a larger discrepancy between their actual (or anticipated) outcomes and the outcomes to which they feel entitled.…”
Section: Methodsmentioning
confidence: 99%
“…Classic research relating macroeconomic downturns to hate crimes (e.g., Hepworth & West, 1988) as well as evidence from the analysis of national surveys indicating a strong correlation between change in the rate of unemployment over time and the level of popular opposition toward immigrants and immigration policy (see Palmer, 1996) suggest that in the RD condition, students will express more negative attitudes toward outgroups (see also Krahn & Harrison, 1992). As Gurr (1970) or Davies (1962) would argue, when economic conditions are getting worse, people may perceive a larger discrepancy between their actual (or anticipated) outcomes and the outcomes to which they feel entitled.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have examined how perceived reduction in standard of living during an economic recession influences distress. A survey conducted by Krahn and Harrison (1992) during a 1980s recession in Alberta, Canada, is an exception. Building on relative deprivation theory, this study found that working-class people who perceived a reduction in their standard of living in the recession indicated more support for government redistribution, suggesting that experiencing a reduction in living standard in a crisis can trigger grievance toward the social order.…”
Section: Comparisons In the Social Context Of An Economic Crisismentioning
confidence: 99%
“…Research generally finds harmful effects of recessions on mental health, although there is heterogeneity in the findings (Zivin et al, 2011). Thus, research indicates that crises generally increase distress, but since it has mostly focused on the (aggregate- or individual-level) effects of economic factors (see Krahn and Harrison, 1992), we know little about the mechanisms through which crises influence distress (see Hedström and Swedberg, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The present becomes the baseline for comparisons with the past or the expected future situation of the in‐group. According to analysts, temporal comparisons are especially important in periods of social change (Albert, 1977; Brown & Middendorf, 1996; Hinkle & Brown, 1990; Mummendey, Mielke, Wenzel, & Kanning, 1992), or in times of economic difficulties (Krahn & Harrison, 1992). For instance, temporal comparisons allow people to re‐evaluate their group position in a drastically changed social environment.…”
mentioning
confidence: 99%